Global Potentials and Costs of Synfuels via Fischer–Tropsch Process - Patrick Buchenberg; Thushara Addanki; David Franzmann; Christoph Winkler; Felix Lippkau; Thomas Hamacher; Philipp Kuhn; Heidi Heinrichs; Markus Blesl (Energies, 2023)
This paper presents the potentials and costs of synthetic fuels (synfuels) produced by renewable energy via PEM water electrolysis and the subsequent Fischer–Tropsch process for the years 2020, 2030, 2040, and 2050 in selected countries across the globe. The renewable energy potential was determined by the open-source tool pyGRETA and includes photovoltaic, onshore wind, and biomass. Carbon dioxide is obtained from biomass and the atmosphere by direct air capture. The potentials and costs were determined by aggregating minimal cost energy systems for each location on a state level. Each linear energy system was modelled and optimised by the optimisation framework urbs. The analysis focused on decentralised and off-grid synthetic fuels’ production. The transportation costs were roughly estimated based on the distance to the nearest maritime port for export. The distribution infrastructure was not considered since the already-existing infrastructure for fossil fuels can be easily adopted. The results showed that large amounts of synthetic fuels are available for EUR 110/MWh (USD 203/bbl) mainly in Africa, Central and South America, as well as Australia for 2050. This corresponds to a cost reduction of more than half compared to EUR 250/MWh (USD 461/bbl) in 2020. The synfuels’ potentials follow the photovoltaic potentials because of the corresponding low levelised cost of electricity. Batteries are in particular used for photovoltaic-dominant locations, and transportation costs are low compared to production costs.